Impact of the mouse estrus cycle on cannabinoid receptor agonist‐induced molecular and behavioral outcomes - Hye Ji J. Kim; Ayat Zagzoog; Tallan Black; Sarah L. Baccetto; Udoka C. Ezeaka; Robert B. Laprairie (Wiley, 2022)
Abstract Sexual dimorphisms are observed in cannabinoid pharmacology. It is widely reported that female animals are more sensitive to the cataleptic, hypothermic, antinociceptive, and anti‐locomotive effects of cannabinoid receptor agonists such as CP55,940. Despite awareness of these sex differences, there is little consideration for the pharmacodynamic differences within females. The mouse estrus cycle spans 4-5 days and consists of four sex hormone‐mediated phases: proestrus, estrus, metestrus, and diestrus. The endocannabinoid system interacts with female sex hormones including β‐estradiol, which may influence receptor expression throughout the estrus cycle. In the current study, sexually mature female C57BL/6 mice in either proestrus or metestrus were administered either 1 mg/kg i.p. of the cannabinoid receptor agonist CP55,940 or vehicle. Mice then underwent the tetrad battery of behavioral assays measuring catalepsy, internal body temperature, thermal nociception, and locomotion. Compared with female mice in metestrus, those in proestrus were more sensitive to the anti‐nociceptive effects of CP55,940. A similar trend was observed in CP55,940‐induced catalepsy; however, this difference was not significant. As for cannabinoid receptor expression in brain regions underlying antinociception, the spine tissue of proestrus mice that received CP55,940 exhibited increased expression of cannabinoid receptor type 1 relative to treatment‐matched mice in metestrus. These results affirm the importance of testing cannabinoid effects in the context of the female estrus cycle.